Structural framework conditions and individual motivations for youth-mobility: A macro-micro level approach for different European country-types - Hemming, Karen; Schlimbach, Tabea; Tillmann, Frank; Nienaber, Birte; Roman, Monica; Skrobanek, Jan (Migration Letters, 2018)
European youth mobility seems to be fostering Europe’s unequal pace of integration, which sees certain countries benefit at the expense of others (Ohmacht et al., 2009; van Mol & Timmerman, 2014). Using a comparative approach, the paper aims to relate a macro-level country-typology focussing on human capital with individual mobility-motivations on the micro-level. Our methodological approach is based on a secondary macro-data analysis and analyses of mobility-motivations of young people (micro-data) deriving from qualitative (N=152) and quantitative data (N=5,499) collected in six European countries. In order to examine correspondence between macro-conditions and micro-aspects, we relate information on mobility-motivations to the country-typology by allocating mobile youth to the respective types of their home country. The results show that the country-types compose different opportunity structures, which are reflected in individual motivations. Accordingly, different country-types can be seen as an example of the heterogeneity and inequality of European social and territorial mobility frames.